Pengaruh Proses Pertambangan Tradisional Wonocolo Terhadap Kandungan Nitrogen (N), Phosphor (P), Kalium (K) Di Tanah Sekitar Area Pertambangan - Nindy Callista Elvania (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
The traditional mining process in Wonocolo Village can have a significant impact on the quality of the soil around the mining area. This study aims to determine the effect of traditional mining processes on nitrogen, phosphorus, and potassium content in soil. Because the content of Nitrogen (N), Phosphorus (P), Potassium (K) has an important role in soil fertility and plant growth, and can affect agricultural productivity and environmental sustainability in traditional mining areas. The method used in testing N, P, K in the soil is using a soil test tool. The results of testing soil quality in mining activities show that the parameters Nitrogen (N), Phosphorus (P), Potassium (K) have low values, this can be seen when testing using a solution of Nitrogen (N), Phosphorus (P), Potassium (K) discoloration of the soil cannot be seen. So that the results obtained are that soil pollution caused by traditional Wonocolo mining can be managed with bioremediation and phytoremediation techniques where these techniques are considered the most efficient and environmentally friendly in an effort to reduce soil pollution.